Kept boy [videorecording (DVD)] - Phillips, Jon Paul; Riefenstein, Thure; Audino, Greg (Breaking Glass Pictures, 2017)
Interior designer and reality show star Farleigh Knock has a knack for keeping beautiful things, like adonic Dennis, around his home. So, when Farleigh gives him an unthinkable ultimatum for his 30th birthday, to get a job or get out, Dennis goes from kept boy to lost man.